Toward Better Constrained Scattering Models for Natural Ice Crystals in the Visible Region. Issue 2 (10th January 2023) - Xu, Guanglang; Waitz, Fritz; Wagner, Shawn; Nehlert, Franziska; Schnaiter, Martin; Järvinen, Emma
Abstract: In this work, we introduce a method for constraining the optical scattering models of natural ice crystals based on in‐situ measurements. Specifically the measured angular scattering functions for ice crystals can be used to compute a set of the asymmetry parameter ( g ) and the corresponding complexity parameter ( C p ). It is demonstrated that the g ‐ C p relation can give valuable information on the morphology of ice crystal. The validity of the methods is shown from theoretical perspectives and the geometric‐optics ray‐tracing simulations. As an application, we investigate rimed ice crystals from in‐situ measurements and found that (a) the C p parameter is very well correlated with the surface riming degree and (b) only those models with both roughness and internal scattering can explain the observed g ‐ C p relation for rimed particles. Plain Language Summary: Light scattering models of ice crystals are important for remote sensing and climate studies. Yet, many physical parameters, such as shape, aspect ratio, and inhomogeneity of the ice crystal can impose significant uncertainty in the single‐scattering properties predicted by light scattering models. To reduce such uncertainty and constrain the physical parameters in modeling, we introduce a novel method by analyzing the in‐situ measurement of the phase functions of ice crystals. We demonstrate the validity and usefulness of the method using both geometric ray‐tracing simulations and a case study on rimed crystals from two campaigns. Key Points: A method is developed for analyzing in‐situ polar nephelometer measurements, aiming for constraining the light scattering models for natural ice crystal Validity of the method is demonstrated by geometric‐optics ray‐tracing simulations and in‐situ measurements A case study of rimed crystals measured in‐situ during two aircraft field campaigns using the Particle Habit Imaging and Polar Scattering probe is presented